Aesthetic Modernity and Its Dilemmas: Art between the Demand for Independence and the bet of Penetrating Public Space - Chebli, Ahmed (Arab Journal for Sciences and Research Publishing, 2025)
This study aimed to identify the significance of aesthetic modernity and to analyze its main dilemmas, namely: art in the world, art and the public sphere, and art and artificial intelligence. To achieve this, the study adopted the analytical method, first by examining the nature of the artwork in terms of quantity, quality, direction, and addition, as presented by Kant in Critique of Judgment. It then analyzed the relationship between art and the world from a phenomenological perspective, and the relationship between art and the public sphere from the Frankfurt School’s view, in addition to exploring the impact of artificial intelligence on artistic production. The study drew upon Kantian, Phenomenological, and Frankfurt perspectives due to Kant’s role in founding modern aesthetics, Phenomenology’s view of the intimate bond between art and the world, and the Frankfurt School’s critique of art’s role in the public sphere. The study concludes that aesthetic modernity marked a transformation in the view of art, shifting it from submission to external dictates toward an expression of the artist’s own capabilities. Nevertheless, while this independence underscores the subjective expression of art, it does not undermine its ability to reflect the world, permeate the public sphere, and critique reality. Furthermore, the study finds that while the commodification of art through artificial intelligence poses a risk of ideology, this does not erase its potential to unveil deception and contribute to liberation from domination. Therefore, the study advocates maintaining a distance between art and ideology to enable it to critique, innovate, and illuminate society instead of serving ideology’s goals in the public sphere.